Lichenoid drug eruption due to eprosartan/hydrochlorothiacide - Ricardo Ruiz-Villaverde; Manuel Galan-Gutierrez (PAGEPress Publications, 2011)
We report a case of a 66-year-old male who developed an itchy eruption while taking an antihypertonic drug containing eprosartan and hydrochlorothiacide after sun exposure. The lesions resembled a lichenoid appearance that was confirmed by the histological study. There are few reports in the literature of lichenoid reactions to these compounds, so we review the characteristics of themselves as a potencial cause of drug eruptions.